Psalmody and Poetry in Old Testament Ethics. Edited by Dirk J. Human - Houston, Walter J. (The journal of theological studies, 2013)
This volume represents the proceedings of an international seminar at the University of Pretoria in August 2008. All but two of the contributors are based at South African universities, mostly at Pretoria, and all but three are African; so while it is fair to describe the collection as international, it also has a distinctly African flavour, especially in the three contributions by black Africans. All the contributors write in English. The title, as well as being awkward, is slightly misleading: there is no consideration of poetry qua poetry in these essays., The editor’s preface summarizes each of the contributions at some length. He has no substantive contribution of his own.